2017
DOI: 10.1097/mej.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of delirium, implementation and validation of the CAM-ICU in elderly Emergency Department patients

Abstract: The diagnosis rate of delirium after implementation of the CAM-ICU was three-fold higher than before. The CAM-ICU is a reliable screening tool in the ED, with high sensitivity, specificity, and positive and negative predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
0
15
1
2
Order By: Relevance
“…Our experience showed that there was an increase in the number of patients diagnosed after the implementation of the instrument, as confirmed by the indicator unit. This situation was similar in other services (8)(9) . The nurse has an important role in the prevention and early identification of the dysfunction, because it establishes a close proximity to the patient that allows recognition and, thus, can contribute to improved quality of care and, consequently, its results (3) .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our experience showed that there was an increase in the number of patients diagnosed after the implementation of the instrument, as confirmed by the indicator unit. This situation was similar in other services (8)(9) . The nurse has an important role in the prevention and early identification of the dysfunction, because it establishes a close proximity to the patient that allows recognition and, thus, can contribute to improved quality of care and, consequently, its results (3) .…”
Section: Discussionmentioning
confidence: 55%
“…Health services in which the tool was implemented revealed an increase in the diagnosis of delirium,, as well as an optimized care. These factors contributed to the decision of the group to instrumentalize the nurses and implement the systematic screening of delirium (8)(9) . Studies have shown that the records made by nurses regarding delirium were important because of their impact on the outcomes of care (6,10) .…”
Section: Introductionmentioning
confidence: 99%
“…(811) Unfortunately, literature is scant on the incidence of ED-stay associated delirium and its potential impacts on hospital LOS, functional status, and unplanned ED returns in Canadian settings. The onset of such complication in the ED could influence hospital LOS (15) and reflect back on ED crowding.…”
Section: Discussionmentioning
confidence: 99%
“…Since this review, a few studies prospectively assessed the incidence of delirium in the ED have been published. (811) To our knowledge, none were conducted in a Canadian ED setting.…”
Section: Introductionmentioning
confidence: 99%
“…The Confusion Assessment Method (CAM) is a good tool for the identification of delirium [71]. The CAM for the Intensive Care Unit (CAM-ICU) [72] has shown to have a better capacity to diagnose delirium in older patients in the ED [73]. It is recommended that cognitive status is evaluated, after ruling-out delirium, at the time of the first visit, or failing that, on ward admission.…”
Section: Evaluation Of Frailty In Older Patients With Ahfmentioning
confidence: 99%